Sustaining Competitiveness Through product Development Activities Within Malaysian Automotive Suppliers - Mohamad, Norizah; Othman, Siti Norezam; Abu Bakar, Nooh; Muhamad, Mohd Razali (School of Business and Management Institut Teknologi Bandung, 2008)
The local automotive suppliers are facing a number of important challenges such asglobalisation, new requirement in market specifications and the competition brought about by theAsean Free Trade Area (AFTA) agreements. In an effort to enhance the competitiveness of themanufacturing sector, the government has implemented the Second Industrial Master Plan, IMP2(1996-2005). The focus of the IMP2 is more on innovation and applications of new technologies, sothat industries can move up the value chain of their activities. Innovative capabilities achieved fromcompanies’ new product development activities have been recognized to be crucial for companies tosustain their competitiveness and organisational success. The importance of product development ismost obvious in the context of the discussion on the competitiveness of the Malaysian automotivesuppliers. The study will focus on the small medium enterprises (SMEs) that make up more than 60 %of these automotive suppliers. The study is to determine the extensiveness of the suppliers’ productdevelopment activities by examining the involvement of the suppliers in customer’s productdevelopment activities. Consequently, the impact of this involvement to the competitiveness of thesuppliers is examined. The results were established based from a survey to parts and componentssuppliers of Proton, the Malaysian car national assembler. The study has shown that the SMEs wereinvolved from the early stages of the product development process that is during the design stage. Theproduct development efforts have shown to contribute towards increasing firms’ market share andfirms were also able to gain a better understanding of future product demand. A significant number ofthe suppliers have managed to penetrate the export market. Unfortunately, among the respondents,there is only one system supplier. This indicates that, either the technological capabilities of theSMEs still needed upgrading for the requirement as a system suppliers or it may not be the onlydeciding factor for suppliers to be chosen as system suppliers. It is intended that this paper shouldserve to inform management in particular the suppliers on the present status of the SMEs in seekingto improve their competitiveness from product development effort.Keywords: Product development, SMEs, automotive suppliers, competitiveness